2012
DOI: 10.1007/s10552-012-9981-2
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variants in IGF-I, IGF-II, IGFBP-3, and adiponectin genes and colon cancer risk in African Americans and Whites

Abstract: Purpose Evaluating genetic susceptibility may clarify effects of known environmental factors and also identify individuals at high risk. We evaluated the association of four insulin-related pathway gene polymorphisms in insulin-like growth factor-1 (IGF-I) (CA)n repeat, insulin-like growth factor-2 (IGF-II) (rs680), insulin-like growth factor binding protein-3 (IGFBP-3) (rs2854744), and adiponectin (APM1 rs1501299) with colon cancer risk, as well as relationships with circulating IGF-I, IGF-II, IGFBP-3, and C-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
1
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 79 publications
3
41
1
1
Order By: Relevance
“…A recently published case–control study that included African-American (231 cases and 306 controls) and white (297 cases, 530 controls) patients assessed the relationships between IGF-1 (CA) 19 , IGF-2 Apa1 , IGFBP-3, and APN gene polymorphism and CRC risk 169. In white patients only, those homozygous for the IGF-1 (CA) 19 repeat exhibited an increased CRC risk (OR=1.77, 1.15 to 2.73), while those carrying the IGF-2 Apa1 A-variant exhibited a decreased CRC risk (OR=0.49, 0.28 to 0.88) 169.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published case–control study that included African-American (231 cases and 306 controls) and white (297 cases, 530 controls) patients assessed the relationships between IGF-1 (CA) 19 , IGF-2 Apa1 , IGFBP-3, and APN gene polymorphism and CRC risk 169. In white patients only, those homozygous for the IGF-1 (CA) 19 repeat exhibited an increased CRC risk (OR=1.77, 1.15 to 2.73), while those carrying the IGF-2 Apa1 A-variant exhibited a decreased CRC risk (OR=0.49, 0.28 to 0.88) 169.…”
Section: Resultsmentioning
confidence: 99%
“…In white patients only, those homozygous for the IGF-1 (CA) 19 repeat exhibited an increased CRC risk (OR=1.77, 1.15 to 2.73), while those carrying the IGF-2 Apa1 A-variant exhibited a decreased CRC risk (OR=0.49, 0.28 to 0.88) 169. The investigators also suggested specific variants of IGF-2R might be associated with increased CRC risk (OR=2.2, 0.9 to 5.4), perhaps explained by modulating circulating levels of IGF-2 170…”
Section: Resultsmentioning
confidence: 99%
“…Several genetic polymorphisms in the IGFBP-3 gene have been identified for predicting the development, progression, and clinical outcomes of colorectal cancer, but A-202C and C2133G were the most common ones (Poole et al, 2012). Many previous genetic studies have suggested that IGFBP A-202C and C2133G polymorphisms play an important role in colorectal carcinogenesis (Le Marchand et al, 2005;Morimoto et al, 2005;Samowitz et al, 2006;Slattery et al, 2006;Xiang et al, 2009;Feik et al, 2010;Keku et al, 2012;Ollberding et al, 2012), while other studies found no convincing evidence of these polymorphisms in increasing the risk of colorectal cancer (Slattery et al, 2004;Wong et al, 2005;Pechlivanis et al, 2007). This controversy could be explained with several reasons, including the differences in study design, sample size, ethnicity, and statistical method.…”
Section: Discussionmentioning
confidence: 99%
“…Of these articles, 66 were excluded after reviewing their titles and key words; then, abstract and full text were reviewed, and another 68 papers were excluded. Eleven case-control studies met our inclusion criteria (Le Marchand et al, 2005;Morimoto et al, 2005;Wong et al, 2005;Samowitz et al, 2006;Slattery et al, 2004Slattery et al, , 2006Pechlivanis et al, 2007;Xiang et al, 2009;Feik et al, 2010;Keku et al, 2012;Ollberding et al, 2012). The publication years of the involved studies ranged from 2004 to 2012.…”
Section: Baseline Characteristics Of Included Studiesmentioning
confidence: 99%
“…Partida-Perez et al, 2010;He et al, 2011;Liu et al, 2011;Keku et al, 2012;Tsilidis et al, 2009;Wang et al, 2009), respectively…”
unclassified